O-018 Bridging thrombolysis does not increase complications of rescue intracranial stenting. (23rd July 2022) - Akbik, F; Alawieh, A; Grossberg, J; Cawley, C; Kinariwala, J; Jabbour, P; Maier, I; Wolfe, S; Rai, A; Starke, R; Gory, B; Psychogios, M; et al.
Abstract : Introduction: Given the mixed results of recent clinical trials, the role of bridging therapy with intravenous thrombolysis (IVT) in patients undergoing mechanical thrombectomy (MT) remains contested. These results highlight the need to identify subgroup specific strategies to optimize patient selection. Patients undergoing MT for intracranial atherosclerotic disease (ICAD) are more likely to require rescue intracranial stenting and an attendant load of dual antiplatelet drugs. Whether bridging thrombolysis increases hemorrhagic complications in patients requiring rescue intracranial stenting is unclear and may affect frontline thrombolysis decisions in patients with suspected ICAD related large vessel occlusions (LVOs). Here we determine whether bridging therapy modifies procedural and clinical outcomes in patients requiring rescue intracranial stenting after a failed MT. Methods: We performed a retrospective cohort study of the Stroke and Aneurysm Registry (STAR) from January 2015 to December 2021 and identified 8, 988 patients who underwent MT, 108 (1.2%) of underwent rescue intracranial stenting after failed MT for anterior circulation LVOs. Prospectively defined baseline characteristics and clinical outcomes were compared. Results: 108 patients underwent rescue stenting, 32 (29.6%) who received IVT and 76 (70.4%) did not. Patients receiving IVT presented significantly earlier (700 [312–1178] vs 242 [179–333] min, p<0.001), but were otherwise comparable in baseline demographics. A similar number of mechanical thrombectomy passes were employed in both cohorts (3 [2–5] vs 3 [2–5], not significant) with comparable procedural times. Any post-procedural hemorrhage within the first 36 hours was similarly common between both groups (24.6% vs. 31.3%). Symptomatic hemorrhage or type-2 parenchymal hematomas were rare in both groups, with a non-significant trend towards increased events with IVT (2 vs. 4 events, 2.9% vs 12.5%, p=.078). Good functional outcomes, defined as a modified Rankin score of 0–2 measured 90 days post discharge, were comparable between groups (23.7% vs. 37.0%, p=0.209). IVT use did not associate with hemorrhagic complications or good functional outcomes at 90 days in multivariable binary logistic regression analyses. Conclusions: In this international, retrospective cohort study of likely highly-selected patients, IVT exposure did not modify hemorrhagic complications or outcomes in patients requiring intracranial rescue stenting after failed MT. These results are consistent with several randomized clinical trials which did not demonstrate increased hemorrhagic complications in unselected patients undergoing bridging thrombolysis. These data suggest that acute intracranial stenting (with attendant dual antiplatelet loading) may be safe in selected patients exposed to IVT and argue against withholding IVT for patients at higher risk of needing rescue stenting. Disclosures: F. Akbik: None. A. Alawieh: None. J. Grossberg: None. C. Cawley: None. J. Kinariwala: None. P. Jabbour: None. I. Maier: None. S. Wolfe: None. A. Rai: None. R. Starke: None. B. Gory: None. M. Psychogios: None. A. Shaban: None. A. Arthur: None. J. Kim: None. S. Yoshimura: None. P. Kan: None. R. DeLeacy: None. I. Fragata: None. A. Polifka: None. J. Osbun: None. T. Dumont: None. R. Williamson: None. R. Crosa: None. M. Levitt: None. M. Moss: None. M. Park: None. W. Casagrande: None. S. Chowdhry: None. A. Spiotta: None. A. Spiotta: None. B. Howard: None.